Marketing of Transport Services and Millenium Development Goals; the Case of Keke Napep Initiatives in Lagos, Nigeria (Global Journal of Management and Business Research, 2013)
This study examined the role of marketing of transport services in the realization of a millennium development goal; poverty alleviation. KEKE-NAPEP initiative was one of the poverty eradication programmes in Lagos state, Nigeria. The study examined the significance of the relationship between the initiative and (1) poverty level (2) standard of living and (3) level of unemployment. The study employed survey research and purposive sampling technique was used to identify users of KEKE-NAPEP in Lagos State. The findings of the study revealed that although the initiative improves the standard of living of people and has negative relationship with level of unemployment, the initiative is not significantly related with the poverty level of the people of Lagos state. Based on these findings, conclusion was drawn and relevant recommendations were made. If the initiative must be successful in reducing the poverty, it is recommended that marketing techniques and strategies be employed and engaged.
Keywords: millennium development goals; poverty; standard of living